ENGINEERING SOLUTIONS FOR THE SAFETY OF HYDRAULIC STRUCTURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The proper and rational use of water resources in Uzbekistan requires the use of hydraulic structures, but if the safety solutions of such facilities are not calculated correctly, tragic situations and man-made emergencies can occur. This article provides an analysis of engineering solutions for hydraulic structures and water safety engineering solutions based on the requirements for them.